2023
DOI: 10.3390/antiox12051103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant Stability of Meat Pâté with Allium cepa Husk Extract

Abstract: Antioxidants play a very important role in the food industry. Recently, both science and industry have shown substantial preference for natural antioxidants, including searching for antioxidant substances from natural sources without undesirable side effects. The purpose of this study was to evaluate the effect of adding Allium cepa husk extract at a volume of 68 or 34 μL/g of unsalted blanched materials to replace 34% and 17% of the beef broth, respectively, which corresponded to a total antioxidant capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Since the pate preparation technology included a hot chopping step, during which the minced pate was homogenized for 5 minutes at a temperature above 40 °C, the ethanol contained in the extract evaporated. In addition, in [24], we demonstrated that the addition of OHE to the formulation of meat pates led to a decrease in the mass fraction of moisture by 4.17% (Sample 1) and by 1.47% (Sample 2).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Since the pate preparation technology included a hot chopping step, during which the minced pate was homogenized for 5 minutes at a temperature above 40 °C, the ethanol contained in the extract evaporated. In addition, in [24], we demonstrated that the addition of OHE to the formulation of meat pates led to a decrease in the mass fraction of moisture by 4.17% (Sample 1) and by 1.47% (Sample 2).…”
Section: Resultsmentioning
confidence: 75%
“…It was determined that reducing the concentration of OHE introduced into the meat product by 50% significantly reduced the contribution of the plant extract to TAC DPPH , as evidenced by the excess of the difference between Sample 1 and the control pate (∆(S1-C)) and the differences between Sample 2 and the control at day 0 of approximately 1.7 times. Based on the results of the experiment, it was determined that within 14 days of storage, the addition of OHE to the formulation of meat pate provides a significantly increased TAC in relation to nitrogen-containing free radicals in comparison with the control sample, with previously proven reduction in oxidative spoilage presented in [24]. Other researchers have shown the effectiveness of using peanut skin extract to inhibit oxidative spoilage in meat burgers, i. e. the reduction of lipid and protein oxidation products [31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations